Assessment of the dose burden and health status of the uranium processing workers of the Republic of Kazakhstan - Aumalikova, M; Ibrayeva, D. S.; Ilbekova, K.; Kazymbet, P. K.; Bakhtin, M. M. (Eurasian Journal of Physics and Functional Materials, 2026)
The main objective of current study is to assess the dose burden and health status of workers at the uranium processing hydrometallurgical plant in order to develop measures aimed at reducing their incidence. This article presents the results of radiation monitoring and data on the health status of workers at the hydrometallurgical plant of the Stepnogorsk Mining and Chemical Combine (SMCC). The data of the accumulated effective dose for the entire length of service, as well as data on the incidence rate for the period 2013-2019, obtained from the base of the Industrial Radiation and Epidemiological Register, have been analyzed. Based on the results of measurements of the uranium content in urine, the expected effective dose of internal irradiation of the enterprise personnel was calculated. The assessment of the health status of workers was carried out based on the materials of outpatient and hospital visits, as well as the results of mandatory periodic medical examinations over the past 5 years. Based on the results, an excess of the expected effective dose of internal irradiation was revealed based on the analysis of a urine sample by 3 times. The most typical for the studied contingent of the main group turned out to be diseases of the eye and its adnexa (23%). Recommended Citation Aumalikova, M. N.; Ibrayeva, D. S.; Ilbekova, K.; Kazymbet, P. K.; Bakhtin, M. M.; Janabaev, D. D.; and Altaeva, N. Z. (2020) "Assessment of the dose burden and health status of the uranium processing workers of the Republic of Kazakhstan," Eurasian Journal of Physics and Functional Materials: Vol. 4: No. 4, Article 7. DOI: https://doi.org/10.29317/ejpfm.2020040407